Validation and evaluation of diagnostic tests for Schistosoma mansoni in Brazil: The ValidaXisto study protocol - Cristina Toscano Fonseca; Rosiane A. da Silva-Pereira; Roberta Lima Caldeira; Wilma Patrícia de Oliveira Santos Bernardes; Clarice Carvalho Alves; Taynãna César Simões; Wagnner José Nascimento Porto; Edward José Oliveira (PLoS ONE, 2026)
The persistence of schistosomiasis as a serious public health problem can be attributed, in part, to the lack of more accurate diagnostic techniques, particularly in areas with low prevalence and low parasitic burden. Thus, an effective diagnostic tool with broad applicability for detecting active infections in both high- and low-prevalence settings, as well as for accurately monitoring cure after therapeutic interventions, represent an instrument of utmost importance for controlling disease transmission. Therefore, we propose evaluating different commercial tests for schistosomiasis diagnosis identified through a review of all tests registered to be used in Brazil by the Brazilian regulatory agency (ANVISA) and those registered by other regulatory agencies, as well as prototypes of tests under development. In addition, we propose the development and evaluation of molecular diagnostic methodologies for schistosomiasis using different biological samples (stool, blood, and urine) from individuals living in an endemic area. The Kato-Katz technique, with 18 slides per stool sample, will be used as the reference test for definition of schistosomiasis cases. The performance of the evaluated techniques will be compared with respect to sensitivity, specificity, accuracy, positive and negative likelihood ratios, agreement with the reference test, cost, time, and ease of execution. The effectiveness and feasibility of these diagnostic tests will be assessed to recommend their incorporation into the schistosomiasis surveillance actions of the Ministry of Health within the Brazilian Unified Health System (SUS) in the short to medium term, considering the conditions faced by surveillance programs within Primary Health Care.